Characterization of Filoplan and Endophytic Mold Isolates Avicennia marina from Mangrove Area, Semarang - Wahyu Aji Mahardhika; Arina Tri Lunggani; Isworo Rukmi; Dicky Setiawan; Ansalakhul Balayatin NiÃ¢â¬â¢mah; Nur Amalia Firdausa; Dina Devina Anggraeni (Jurnal Biologi Tropis, 2021)
The presence of fungi in nature is very abundant, but at this time it is still necessary to know and explore the various types that are able to live in various places. Fungi can live in plant tissue, known as endophytic fungi, and can also live on the leaf surface of a plant. Avicennia marina lives on the coast and is used to reduce abrasion, besides being able to live in tidal habitats and high salinity levels. This is supported by the plant's physiology and the help of its microbial symbionts, therefore it is necessary to explore fungi, especially fungi that are able to symbionting with these plants because they are thought to be resistant to high levels of salinity. The purpose of this study was to determine the types of molds that have been isolated and are able to live in the tissue and leaf surface of A. marina. Characterization method was reviewed through macroscopic and microscopic morphology using a microscope and compared with literature from various sources. The characterization results of the 12 isolates obtained several genera, including Trichoderma, Aspergillus, Penicillium, Curvularia, Paecilomyces, Talaromyces, Syncephalastrum, and 1 unidentified isolate. These isolates need to be continued with further research to see their ability to produce metabolites and so on.